Learning the vi and vim editors - Robbins, Arnold (O'Reilly Media, 2008)
There's nothing that hard-core Unix and Linux users are more fanatical about than their text editor. Editors are the subject of adoration and worship, or of scorn and ridicule, depending upon whether the topic of discussion is your editor or someone else's. vi has been the standard editor for close to 30 years. Popular on Unix and Linux, it has a growing following on Windows systems, too. Most experienced system administrators cite vi as their tool of choice. And since 1986, this book has been the guide for vi. However, Unix systems are not what they were 30 years ago, and neither is this book.
Print version record
Keywords: UNIX (Computer file); Text editors (Computer programs); Éditeurs de texte (Logiciels); COMPUTERS; Programming Languages; General; vi; Vim